Atorvastatin Induces Mitochondria-Dependent Ferroptosis via the Modulation of Nrf2-xCT/GPx4 Axis - Zhang, Qi; Qu, Hang; Chen, Yinghui; Luo, Xueyang; Chen, Chong; Xiao, Bing; Ding, Xiaowei; Zhao, Pengjun; Lu, Yanan; Chen, Alex F.; Yu, Yu (Frontiers in Cell and Developmental Biology, 2022)
As one of the cornerstones of clinical cardiovascular disease treatment, statins have an extensive range of applications. However, statins commonly used have side reactions, especially muscle-related symptoms (SAMS), such as muscle weakness, pain, cramps, and severe condition of rhabdomyolysis. This undesirable muscular effect is one of the chief reasons for statin non-adherence and/or discontinuation, contributing to adverse cardiovascular outcomes. Moreover, the underlying mechanism of muscle cell damage is still unclear. Here, we discovered that ferroptosis, a programmed iron-dependent cell death, serves as a mechanism in statin-induced myopathy. Among four candidates including atorvastatin, lovastatin, rosuvastatin, and pravastatin, only atorvastatin could lead to ferroptosis in human cardiomyocytes (HCM) and murine skeletal muscle cells (C2C12), instead of human umbilical vein endothelial cell (HUVEC). Atorvastatin inhibits HCM and C2C12 cell viability in a dose-dependent manner, accompanying with significant augmentation in intracellular iron ions, reactive oxygen species (ROS), and lipid peroxidation. A noteworthy investigation found that those alterations particularly occurred in mitochondria and resulted in mitochondrial dysfunction. Biomarkers of myocardial injury increase significantly during atorvastatin intervention. However, all of the aforementioned enhancement could be restrained by ferroptosis inhibitors. Mechanistically, GSH depletion and the decrease in nuclear factor erythroid 2-related factor 2 (Nrf2), glutathione peroxidase 4 (GPx4), and xCT cystine–glutamate antiporter (the main component is SLC7A11) are involved in atorvastatin-induced muscular cell ferroptosis and damage. The downregulation of GPx4 in mitochondria-mediated ferroptosis signaling may be the core of it. In conclusion, our findings explore an innovative underlying pathophysiological mechanism of atorvastatin-induced myopathy and highlight that targeting ferroptosis serves as a protective strategy for clinical application.